THE ORIGINAL TURKISH WORDS IN THE EPOS OF «ǴÁRIP-ASHÍQ» (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
At the present time, a number of changes and developments are observed in the field of science. In addition, new chapters in the knowledge of the black language, learners began to learn. The linguistic diversity of the population is studied in the section of linguistic folkloristics. In this article , we will focus on lexical differences and thematic clusters  in the epos of «Ǵárip-ashıq»  . We have decided to define the original Turkic word for  «Ǵárip-ashıq»   in terms of its rich semitic variations.